Customer satisfaction towards SSM counter physical facilities and front liner attitudes / Hazlina Hamzah - Hamzah, Hazlina (Faculty of Business and Management, 2010)
The Companies Commission of Malaysia ( Suruhanjaya Syarikat Malaysia ) or SSM is a statutory body which regulates companies and businesses. SSM, which came into operation on 16 April 2002, is a statutory body formed as a result of a merger between the Register of Companies ( ROC ) and the Register of Business ( ROB ) in Malaysia. The main activity of SSM is to serve as an agency to incorporate companies and register businesses as well as to provide company and business information to the public. As the leading authority for the improvement of corporate governance, SSM fulfils its function to ensure compliance with business registration and corporate legislation through comprehensive enforcement and monitoring activities to sustain positive developments in the corporate and business sectors of the Nation.